A Variation in 3′ UTR of hPTP1B Increases Specific Gene Expression and Associates with Insulin Resistance - Di Paola, Rosa; Frittitta, Lucia; Miscio, Giuseppe; Bozzali, Maura; Baratta, Roberto; Centra, Marta; Spampinato, Daniela; Santagati, Maria Grazia; Ercolino, Tonino; Cisternino, Carmela; Soccio, Teresa; Mastroianno, Sandra; et al. (American journal of human genetics, 2002)
Protein tyrosine phosphatase 1B ( PTP1B) inhibits insulin signaling and, when overexpressed, plays a role in insulin resistance (Ahmad et al. 1997). We identified, in the 3′ untranslated region of the PTP1B gene, a 1484insG variation that, in two different populations, is associated with several features of insulin resistance: among male individuals, higher values of the insulin resistance HOMA IR index ( P=.006), serum triglycerides ( P=.0002), and total/HDL cholesterol ratio ( P=.025) and, among female individuals, higher blood pressure ( P=.01). Similar data were also obtained in a family-based association study by use of sib pairs discordant for genotype (Gu et al. 2000). Subjects carrying the 1484insG variant showed also PTP1B mRNA overexpression in skeletal muscle (6,166 ± 1,879 copies/40 ng RNA vs. 2,983 ± 1,620; P<.01). Finally, PTP1B mRNA stability was significantly higher ( P<.01) in human embryo kidney 293 cells transfected with 1484insG PTP1B, as compared with those transfected with wild-type PTP1B. Our data indicate that the 1484insG allele causes PTP1B overexpression and plays a role in insulin resistance. Therefore, individuals carrying the 1484insG variant might particularly benefit from PTP1B inhibitors, a promising new tool for treatment of insulin resistance (Kennedy and Ramachandran 2000).